Revisiting the First-Level Digital Divide in the United States: Gender and Race/Ethnicity Patterns, 2007–2012. (August 2015) - Campos-Castillo, Celeste
With the narrowing of Internet access divide, researchers have focused on Internet usage, taking for granted access issues. However, questions remain regarding who has Internet access in the United States: What is the status of the racial divide? Is there still a gender divide? How do Latinos compare to other racial and ethnic minority groups? How does gender intersect with race and ethnicity? I analyze nationally representative data to compare Internet access among adults from 2007 to 2012. I find that women are more likely to report having Internet access than men. Blacks and Latinos are equally likely to report having Internet access, and both groups are less likely to report having Internet access than Whites. Finally, Black men exhibited the greatest increase in access. This research complements Internet usage studies with a recent assessment of Internet access trends, important trends to monitor as policies and technological innovations aim for universal access.